2015
DOI: 10.1111/mve.12147
|View full text |Cite
|
Sign up to set email alerts
|

The influence of household pets on the composition and quantity of allergenic mite fauna within Irish homes: a preliminary investigation

Abstract: Allergenic mites are responsible for inducing hypersensitive reactions in genetically predisposed people worldwide. Mites in dust from 30 Irish homes with pets (dogs, n = 23; cats, n = 7) were compared with those in 30 homes without pets. House dust mites constituted 78% of all mites recorded, with Dermatophagoides pteronyssinus (Acariformes: Pyroglyphidae) representing 57-72% of mites in furniture and mattresses in both home types compared with only 22% of mites in pet beds. Although storage mites accounted f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…Furthermore, other factors may affect the prevalence of mites. As reported by studies from Ireland and Sweden, both storage mites and HDMs are found in home environments. Mattresses, stuffed furniture, household pets and pet beds are sources of both mite types, suggesting that the mites thrive in these environments.…”
Section: Discussionmentioning
confidence: 55%
“…Furthermore, other factors may affect the prevalence of mites. As reported by studies from Ireland and Sweden, both storage mites and HDMs are found in home environments. Mattresses, stuffed furniture, household pets and pet beds are sources of both mite types, suggesting that the mites thrive in these environments.…”
Section: Discussionmentioning
confidence: 55%
“…23 L. destructor, being considered an SM historically found mainly where plant or animal foods are processed and stored, has been detected in significant amounts in house dust from various regions of the world. [24][25][26] Although the pyroglyphid HDM D. pteronyssinus and D. farinae seem to predominate, glyciphagid SM mites, such as L. destructor and B. tropicalis may also be important in some regions. 27 Taking these aspects into account, it is vital to study the clinical relevance of L. destructor.…”
Section: Open Accessmentioning
confidence: 99%
“…Nonetheless, according to increasing evidence, some SMs have penetrated the habitats of HDM [5][6][7][8]. Studies from different countries have shown that IgE-mediated allergy to SM, with Lep d being the most prevalent one, is of considerable importance in both rural and urban populations [9][10][11][12][13][14]. A study conducted along the portuguese region analysed dust samples from houses throughout the territory to better understand the intensity of allergic exposure to HDM and SM.…”
Section: Introductionmentioning
confidence: 99%